Dendritic Cells Therapy with Cytokine-Induced Killer Cells and Activated Cytotoxic T Cells Attenuated Th2 Bias Immune Response. (3rd July 2020) - Li, Changyou; Zhu, Danni; Zhao, Yonghui; Guo, Qingming; Sun, Weihong; Li, Linxi; Gao, Daiqing; Zhao, Peng
ABSTRACT: The aim of this study: The purpose of this study is to investigate whether the DC cells combined with CIK cells (DC/CIK) and DC activated cytotoxic T cells (DC-ACT) treatment can promote antitumor response and change the immune indicators by targeting the heterogeneous tumor cell populations at a system level. Methods: In this study, 112 patients with cancer were assigned to the DC/CIK treatment and 116 patients received the DC-ACT therapy. We detected the lymphocyte subsets and other immune indicators pre- and post-treatment to evaluate the changes of patient's immunity and compare the differences in immune status between two adoptive cellular immunotherapies. Results: DC/CIK therapy elevated the percentage of CD3+ HLA-DR+ T cells, NK cells and several serological cytokines such as IL-2, IL-6 after cell infusion ( p < .05). DC-ACT therapy could increase the total CD3 + T cells, CD8 + T cells, CD3+ HLA-DR+ cells and IL-12 cytokines after cell infusion ( p < .05). The levels of IL-4/IFN-γ, IL-4/IL-12 and IL-6/IL-12 were reduced significantly in the DC-ACT group compared with DC/CIK group. These observations suggested that DC-ACT therapy has more dominance to induce Th1 cytokine response instead of skewing toward the Th2 cytokine profile based on the immunomodulatory properties. Conclusions: These results indicated that DC, CIK, and DC-ACT cells exert anti-tumor activity through the different pathways. Thus, this work may provide valuable insights into the clinical curative effect evaluation of immunocyte therapy and the design of combined immunotherapeutic strategies for malignant tumors.